Наша Родина - Россия - Киктев Сергей Максимович (Энциклопедия подготовки к школе, 2015)
Экземпляры: (20170918) / Инвентарный номер: 1330 / Цена: / Сис.шифр: 26.89(2Рос) / Авт.знак: К 38 / ББК: 26.89(2Рос)